Resilience for disaster risk management in a changing climate: Practitioners' frames and practices. (January 2015) - Aldunce, Paulina; Beilin, Ruth; Howden, Mark; Handmer, John
Highlights: This research is novel as not only investigated how stakeholders frame, but also make sense, of resilience in the context of disaster management and climate change. Stakeholders interviewed construct the meaning of resilience differently and even in contradictory ways, embedded in diverse storylines. Self-reliance emerged as one of the paramount discourse categories but we argue that caution need to be used when promoting values of self-reliance. There is a focus on learning, but it is pertinent to move from experiential learning toward social learning. Abstract: There is a growing use of resilience ideas within the disaster risk management literature and policy domain. However, few empirical studies have focused on how resilience ideas are conceptualized by practitioners, as they implement them in practice. Using Hajer's 'social-interactive discourse theory' this research contributes to the understanding of how practitioners frame, construct and make sense of resilience ideas in the context of changes in institutional arrangements for disaster risk management that explicitly include the resilience approach and climate change considerations. The case study involved the roll out of the Natural Disaster Resilience Program in Queensland, Australia, and the study involved three sites in Queensland. The methods used were observation of different activities and the physical sites, revision of documents related to the Natural Disaster Resilience Program and in-depth semi-structured interviews with key informants, all practitioners who had direct interaction with the program. The research findings show that practitioners construct the meaning of disaster resilience differently, and these are embedded in diverse storylines. Within these storylines, practitioners gave different interpretations and emphasis to the seven discourse categories that characterized their resilience discourse. Self-reliance emerged as one of the paramount discourse categories but we argue that caution needs to be used when promoting values of self-reliance. If the policy impetus is a focus on learning, research findings indicate it is also pertinent to move from experiential learning toward social learning. The results presented in this study provide helpful insights to inform policy design and implementation of resilience ideas in disaster risk management and climate change, and to inform theory.